Water resources ecological footprint in the Yellow river Basin: a two-dimensional decoupling analysis and its change trajectory - Zhao, Xiaojing; Li, Xuke; Xi, Yanling (Frontiers in Environmental Science, 2025)
Water resource scarcity is a major obstacle to the sustainable development of the Yellow River Basin (YRB). Accurately identifying the decoupling pathways of water resources ecological footprint (WEF) and economic growth is crucial in resolving the dilemma of water resource utilization and economic development in the YRB. To explore the decoupling states of WEF and the economic growth in cities within the YRB, this study proposed a new two-dimensional decoupling model with 24 different decoupling states, based on the Tapio decoupling model and the environmental Kuznets curve (EKC) hypothesis. Using the panel data from 60 cities in the YRB from 2010–2021, this study found that the relationship between WEF and per capita GDP followed an N-shape pattern. Decoupling performance shows clear regional differentiation: downstream cities exhibited the best decoupling performance, followed by the midstream cities, while the upstream cities showed the poorest performance. The change trajectory of decoupling states showed a clear tendency toward desirable decoupling: the proportion of cities achieving high-economic-level decoupling states (HE-SD and HE-WD) increased markedly from 18.33% to 43.33%. However, this transition was highly dynamic and non-linear, nearly 95% of cities experienced changes in their decoupling states during the study period. These results highlight the urgency of decoupling water resource utilization from economic growth throughout the YRB. In light of the aforementioned discoveries, this paper proposed corresponding policy recommendations aimed at achieving the ideal decoupling of WEF and economic growth in the Yellow River Basin.